Comparison of Manual Methods of Extracting Genomic DNA from Dried Blood Spots Collected on Different Cards: Implications for Clinical Practice. (July 2013) - Molteni, C.G.; Terranova, L.; Zampiero, A.; Galeone, C.; Principi, N.; Esposito, S.
Isolating genomic DNA from blood samples is essential when studying the associations between genetic variants and susceptibility to a given clinical condition, or its severity. This study of three extraction techniques and two types of commercially available cards involved 219 children attending our outpatient pediatric clinic for follow-up laboratory tests after they had been hospitalised. An aliquot of venous blood was drawn into plastic tubes without additives and, after several inversions, 80 μL were put on circles of common paper cards and Whatman FTA-treated cards. Three extraction methods were compared: the Qiagen Investigator, Gensolve, and Masterpure. The best method in terms of final DNA yield was Masterpure, which led to a significantly higher yield regardless of the type of card (p<0.001), followed by Qiagen Investigator and Gensolve. Masterpure was also the best in terms of price, seemed to be simple and reliable, and required less hands-on time than other techniques. These conclusions support the use of Masterpure in studies that evaluate the associations between genetic variants and the severity or prevalence of infectious diseases.